Unlocking Private Sector Investment for Low-Carbon Transition in South Africa : Assessing Investment Climate for Climate Investments - World Bank (World Bank, Washington, DC, 2021)
Just energy transition is key to South Africa’s inclusive and sustainable growth. It is necessary to unlock large pools of private capital and attract foreign investment to drive low-carbon transition. Despite downside risks, South Africa has strong macroeconomic fundamentals and commitment to improving the overall investment climate. Climate change poses considerable systematic risks, thus needs to be urgently integrated into macroeconomic policy and planning. Harness transition opportunity invest in resilient infrastructure and create market for low-carbon technologies to boost growth and strengthen the macro investment climate. Implement carbon tax effectively and raise policy ambition, supported by a fiscal framework conducive for climate investments, as well as invest tax revenues to support just transition. The current energy crisis presents an opportunity for sector reform, regulatory changes, and use of innovative financial solutions to promote low-carbon private sector investments. The World Bank has developed this discussion paper in response to the government of South Africa’s request to analyze ways in which private capital flows can be catalyzed and leveraged for low-carbon investments. The focus of this paper is on electricity generation sector and the industry sector.